2012
DOI: 10.2807/ese.17.05.20073-en
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic of Mycoplasma pneumoniae infection in Denmark, 2010 and 2011

Abstract: Denmark experienced two waves of Mycoplasma pneumoniae infection during autumn and early winter in 2010 and 2011, respectively. Both affected the whole country. The proportion of positive results was almost the same for both, indicating that the two waves were probably of equal size. High macrolide consumption during the epidemics did not seem to affect levels of macrolide resistance in M. pneumoniae, which remain low in Demark (1% to 3%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 4 publications
3
41
0
7
Order By: Relevance
“…However, information from predominantly northern European countries (Denmark, Finland, the Netherlands, Norway, Sweden, United Kingdom) and the Czech Republic does suggest that the autumn of 2011 had an increase of M. pneumoniae infections reported through the existing surveillance systems. Data from Denmark as presented earlier and in this issue [9,23] and Sweden [24] suggests that the epidemic wave started in 2010. With the results from our study, however, we cannot assess whether the reported increases fit into the expected four-to-sevenyear epidemic waves even though this seems to be indicated by data from Finland, Norway and Denmark in this issue [23,25,26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, information from predominantly northern European countries (Denmark, Finland, the Netherlands, Norway, Sweden, United Kingdom) and the Czech Republic does suggest that the autumn of 2011 had an increase of M. pneumoniae infections reported through the existing surveillance systems. Data from Denmark as presented earlier and in this issue [9,23] and Sweden [24] suggests that the epidemic wave started in 2010. With the results from our study, however, we cannot assess whether the reported increases fit into the expected four-to-sevenyear epidemic waves even though this seems to be indicated by data from Finland, Norway and Denmark in this issue [23,25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Data from Denmark as presented earlier and in this issue [9,23] and Sweden [24] suggests that the epidemic wave started in 2010. With the results from our study, however, we cannot assess whether the reported increases fit into the expected four-to-sevenyear epidemic waves even though this seems to be indicated by data from Finland, Norway and Denmark in this issue [23,25,26]. Institutional settings: infection control guidance for institutional care settings and nosocomial outbreaks, including respiratory tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…This may truly indicate a higher proportion of resistant specimens in this particular outbreak or simply be a function of testing a limited number of patient specimens. In recent years, several reports have documented low levels of macrolide resistance (Յ3%) in M. pneumoniae infections across Europe, including Denmark, France, and Germany, during an active epidemic period (27)(28)(29). A recent report by Ferguson and colleagues documented the first macrolide-resistant M. pneumoniae infections in the United Kingdom in 6 of 32 (19%) patients studied (30).…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, however, M. pneumoniae strains showing resistance to macrolides were isolated from clinical samples obtained from Japanese pediatric patients with pneumonia, and macrolide resistance has become widespread in Japan and China (2-7). Macrolide-resistant (MR) M. pneumoniae is also emerging in pediatric populations in other countries (8)(9)(10)(11)(12)(13). However, data on MR M. pneumoniae have mostly been reported for limited areas (2)(3)(4)(5), and there are no reports on regional differences in the prevalence of MR M. pneumoniae throughout Japan.…”
mentioning
confidence: 93%